Hypoxia induces TWIST-activated epithelial–mesenchymal transition and proliferation of pancreatic cancer cells in vitro and in nude mice - Chen, Shi; Chen, Jiang-zhi; Zhang, Jia-qiang; Chen, Hui-xin; Yan, Mao-lin; Huang, Long; Tian, Yi-feng; Chen, Yan-lin; Wang, Yao-dong (Cancer letters, 2016)
The epithelial–mesenchymal transition (EMT) plays a crucial role in pancreatic ductal adenocarcinoma (PDAC) development and progression. TWIST activated by intra-tumoral hypoxia functions to promote the EMT. We hypothesized that TWIST and the downstream gene pathway could mediate PDAC progression under hypoxia. Therefore, 90 PDAC tissue specimens were immunostained for TWIST and other proteins. Pancreatic cancer cell lines were used for in vitro experiments and nude mice were used to confirm the in vivo data. Expression of TWIST and HIF-1α proteins was significantly upregulated, whereas expression of E-cadherin and p16 was down-regulated in PDAC tissues compared to that of non-tumor tissues and in tumor tissues obtained from patients with tumor involving splenic artery than those without splenic artery involvement. Up-regulated TWIST in tumor tissues were associated with worse prognosis in PDAC patients. The in vitro data showed that HIF-1α-induced TWIST overexpression promoted tumor cell growth and EMT under a hypoxic condition via TWIST interaction with Ring1B and EZH2. In vivo data showed that TWIST overexpression or a hypoxic condition induce xenograft growth, abdominal metastasis and low mouse survival, whereas knockdown of either Ring1B or EZH2 expression suppressed tumor xenograft growth and metastasis and prolonged survival of nude mice. TWIST was the key player in promotion of pancreatic cancer development and metastasis under a hypoxic condition through interaction with Ring1B and EZH2 to regulate expression of E-cadherin and p16 proteins in pancreatic cancer cells. •TWIST overexpression promoted tumor cell growth and EMT under a hypoxic condition.•TWIST is a negative regulator of E-cadherin and P16 in PDAC.•TWIST interacted with Ring1B and EZH2.•TWIST recruited Ring1B and EZH2 to the E-cadherin and p16 promoter regions.